Analisis Peran Kerajaan Aceh Darussalam dalam Perdagangan dan Penyebaran Islam pada Abad ke-16 - Namiyah Fitriani; Taqiyuddin Kabalmay; Reziq Ridho; Lalu Rahmat Sugiar; Inas Salsabila Jannata (Tamadduna: Jurnal Peradaban, 2025)
This research examines the glory of the Kingdom of Aceh Darussalam as a center of trade and the spread of Islam in the 16th century. The object of this research includes factors that contribute to the development of Aceh, including geographical position, the role of merchants and Sufis, the support of local rulers, and a structured system of government. The research method used is a literature study with a descriptive-historical approach, which includes collecting sources, verification, interpretation, and compiling historical narratives. The study results show that Aceh, with its strategic location, is a bustling maritime trade center, attracting traders from different countries. The process of Islamization in Aceh was influenced by the interaction between traders and Sufis and the support of local rulers who strengthened the spread of the religion. Under the leadership of Sultan Iskandar Muda, Aceh reached the peak of its glory, becoming one of the five largest Islamic kingdoms in the world. Despite facing challenges such as internal conflicts and threats from foreign powers, Aceh's cultural and historical heritage remains relevant today. This research is expected to contribute to preserving Islamic historical identity in Indonesia and enriching scientific treasures in Islamic government history.